Effect of Different Feeding Method on Feed Conversion and Growth of Common Carp (Cyprinus carpio) in Floating Net Cage - Utomo, N.B.P; Hasanah, P.; Mokoginta, I. (Jurnal Akuakultur Indonesia, 2005)
This experiment was conducted to evaluate the effectiveness of two feeding methods commonly used in cage culture of carp Cyprinus carpio at Jatiluhur Lake. The results showed that the application of "at satiation feeding method" was more effective than "fixed method" (8% of body weight) indicating with food conversion ratio of 1.79 versus 1.84 and daily growth rate of 3.79% versus 3.42%. Keywords: common carp, Cyprinus carpio, FCR, at satiation, growth, cage culture   ABSTRAK Penelitian ini dilakukan untuk mengevaluasi efektivitas dua metode pemberian pakan yang umum digunakan dalam budidaya keramba jaring apung untuk ikan mas di Waduk Jatiluhur.  Hasil penelitian menunjukkan bahwa pemberian pakan secara satiasi lebih efektif dibandingkan dengan pemberian pakan sebanyak 8% dari bobot biomassa, dengan nilai konversi pakan sebesar 1,79 yang lebih kecil dibandingkan perlakuan pakan sebanyak 8% (1,84) dan pertumbuhan harian sebesar 3,79% (vs. 3,42%). Kata kunci: ikan mas, Cyprinus carpio, FCR, at satiation, pertumbuhan, keramba jaring apung